Access, Participation, Control, and Advantage of Digital-Based Healthcare Service for Women Living with HIV/AIDS - Argyo Demartoto; Bhisma Murti; Sri Hilmi Pujihartati (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
Gender inequality significantly contributes to the increased vulnerability of women living with HIV/AIDS (WLHA), limiting their access to adequate healthcare and exacerbating social stigma. This study explores the dynamics of access, participation, control, and benefit of digital-based healthcare services for WLHA in Surakarta, Indonesia, employing Harvard’s gender analysis framework. It aims to understand how digital health platforms—such as telemedicine, telenursing, telepharmacy, websites, and social media—reshape healthcare engagement for WLHA amidst systemic gender disparities. Using an exploratory qualitative method, data were collected through in-depth interviews, observation, and documentation from key informants including healthcare officials, WLHA, medical workers, and support groups. Analysis followed an interactive model with triangulated sources to ensure data validity. The findings reveal that although digital platforms provide promising access to promotive, preventive, curative, and rehabilitative care, WLHA’s full participation remains hindered by male-dominated control over digital technology, entrenched stigma, and institutional discrimination. However, mobile health (mH) interventions have positively influenced WLHA’s knowledge, behavior, decision-making, and self-efficacy. This study underscores the urgent need for gender-responsive digital health policies and capacity-building strategies that empower WLHA and reduce structural barriers to equitable health access.